2007
DOI: 10.1080/02699050701311034
|View full text |Cite
|
Sign up to set email alerts
|

Case ascertainment in pediatric traumatic brain injury: Challenges in using the NEISS

Abstract: The current approach of pediatric TBI case ascertainment in the NEISS faces some challenges in identifying mild TBI. Future research efforts are needed to refine TBI case ascertainment in the NEISS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 24 publications
1
39
1
Order By: Relevance
“…For this study, cases were assigned a TBI code if the patient received either a (1) diagnosis code for concussion, (2) a body part code for head with a diagnosis code for fracture, or (3) a body part code for head with a diagnosis code for internal injury. 13 The locale where the injury occurred was categorized as sports or recreational place, school, home (home, farm, or mobile home), or other (street/highway, other public property, or industrial place). Case disposition was categorized as hospitalized (treated and admitted for hospitalization, treated and transferred to another hospital, or held for observation) or not hospitalized (treated and released, examined and released without treatment, or left without being seen/left against medical advice).…”
Section: Variablesmentioning
confidence: 99%
“…For this study, cases were assigned a TBI code if the patient received either a (1) diagnosis code for concussion, (2) a body part code for head with a diagnosis code for fracture, or (3) a body part code for head with a diagnosis code for internal injury. 13 The locale where the injury occurred was categorized as sports or recreational place, school, home (home, farm, or mobile home), or other (street/highway, other public property, or industrial place). Case disposition was categorized as hospitalized (treated and admitted for hospitalization, treated and transferred to another hospital, or held for observation) or not hospitalized (treated and released, examined and released without treatment, or left without being seen/left against medical advice).…”
Section: Variablesmentioning
confidence: 99%
“…A dataset of all NEISS cases collected at the hospital in 2008 meeting the TBI definition recommended by Xiang et al [16] was obtained from the CPSC. Although the hospital is a NEISS All Injury Programme (NEISS-AIP) site and the data collected for this study included all injuries, rather than just consumer product-related injuries, the dataset contained additional data not available in the NEISS-AIP public use data files because CDC excludes non-injury cases in their public release of the data (personal communication, Tom Schroeder, July 2013).…”
Section: Definition Of Tbi: Neiss Datamentioning
confidence: 99%
“…The NEISS definition of TBI including only the diagnosis code for concussion resulted in a sensitivity of 38.9%, compared to the sensitivity of 79.6% that was achieved when cases with the body part code equalling head and the diagnosis code equalling internal organ injury were added to the TBI definition. Due to the CDC's classification of fractures to the head as TBIs, Xiang et al [16] suggested that the NEISS definition should be improved by also including cases coded with the body part code for head and the diagnosis code for fracture [1,4]. While some studies have adopted this definition [9][10][11][12][13], no study has specifically evaluated this more comprehensive definition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations